Weak population structure and no genetic erosion in Pilosocereus aureispinus: A microendemic and threatened cactus species from eastern Brazil. - Gulzar Khan; Paulianny M Ribeiro; Isabel A S Bonatelli; Manolo F Perez; Fernando F Franco; Evandro M Moraes (PLoS ONE, 2018)
Succulent cacti (Cactaceae) are among the most threatened taxonomic groups assessed to date. Here we evaluated the genetic diversity and population structure of a narrow endemic columnar cactus Pilosocereus aureispinus. This species is only found in a small area of c. 300 km2 of rocky savanna from eastern Brazil and it is currently classified as vulnerable (VU) on the International Union for Conservation of Nature (IUCN) red list. Eight microsatellite loci were genotyped for 91 individuals from four localities of the known P. aureispinus range. In contrast with expectations for narrow endemic species, we found relatively high levels of genetic diversity (e.g., HE = 0.390 to 0.525; HO = 0.394 to 0.572) and very low population structure based on the variation of six loci. All the analyzed individuals were clustered in one unique genetic group in assignment tests. We also generated the sequences of two plastid markers (trnT-trnL and psbD-trnT) and found no variation on a subsample of 39 individuals. We used Landsat 8 images and Normalized Difference Vegetation Index to estimate a potential extent of occurrence of c. 750 km2 for this species. Our results showed that P. aureispinus is not suffering from erosion of nuclear genetic variability due to its narrow distribution. However, we advocate that because of the extremely limited extent of occurrence, the ongoing anthropogenic disturbances in its habitat, and phylogenetic distinctiveness of P. aureispinus, this species should be classified as endangered (EN) on the IUCN Red List.